Adaptation of Flexible Working System to Support Team Productivity in Pandemic-Changing Situations - Christmy Handiyanto; Denisha Munaf; Ferdian Suria; Indra Syahruzza; Rahajeng Tyas Astari (Indonesian Business Review, 2023)
This research aims to study the adaptation of a flexible working system and what supports team productivity in pandemic-changing situations. It uses qualitative research by performing in-depth interviews and focuses on the interviews of eight managers of four supporting functions: IT, Finance, HR, and Legal, in three leading companies in Indonesia The finding in this research shows the companies have experienced and still adapting to formulate a new working system. To support team productivity in the new working system, several factors need to be addressed, such as: facilities and technical support, the adaptation of SOP and job function, supervisor control, company and team agility, improved communication, work environment, and self-motivation. The new working system is expected to bring impact: improve productivity, cost reduction, environmental improvement, and employee well being. Further quantitative research is recommended to validate the factors supporting a flexible working system that influence team productivity and the expected impact. This study is expected to help management or organization to a better understanding of factors supporting the adaptation of the flexible working system needed to maintain team productivity in this changing situation. To the best of our knowledge, this research is the first to study the adaptation of a flexible working system and what factors are needed to support team productivity in pandemic-changing situations.